New records of introduced species in the Mediterranean Sea (February 2025) - PERIKLIS KLEITOU; DARYL AGIUS; SENCER AKALIN; MARCO ALBANO; IZDIHAR ALI AMMAR; COŞKUN MENDERES AYDIN; ERNESTO AZZURRO; LUCIO BELLOMO; ANDREA BONIFAZI; GIOELE CAPILLO; FABIO CROCETTA; IVAN CVITKOVIĆ; et al. (Mediterranean Marine Science, 2025)
This Collective Article compiles information on nineteen (19) species recorded in seven (7) Mediterranean countries (Croatia, Cyprus, Italy, Malta, Slovenia, Syria, and Türkiye) and across four major sub-basins (Adriatic, Western, Central, and Eastern Mediterranean). The documented taxa represent eight (8) phyla: Annelida (four species), Arthropoda (three), Bryozoa (one), Chordata (two), Cnidaria (two), Mollusca (five), Chlorophyta (one), and Ochrophyta (one). Observations originated from both dedicated scientific surveys (including trawl sampling, van Veen grabs, and harbor-wall scraping) and citizen science initiatives by divers, shell collectors, and recreational fishers. Significant first records include Notomastus aberans (Slovenia), Paraprionospio coora (Italy), Polydora cornuta (Tyrrhenian Sea), Coleusia signata (Cyprus), Penaeus aztecus (Malta), Pleopis schmackeri (Syria), Pteragogus trispilus (Italy), Triacanthus biaculeatus (Türkiye), Oculina patagonica (Syria), and Watersipora subatra (Slovenia). In the Mollusca group, Conomurex persicus extends its known range westward to the Messina Strait (southern Italy), and Sepioteuthis lessoniana is recorded for the first time in Italian waters. Additional first reports for Türkiye include Alveinus miliaceus and Retusa desgenettii in the Turkish Levantine Sea. The species Uroteuthis (Photololigo) arabica represents a first record for the entire Mediterranean basin. Finally, Colpomenia peregrina (Chlorophyta) and Caulerpa taxifolia (Ochrophyta) highlight ephemeral “boom-and-bust” occurrences in Croatia, raising questions about transient invasive dynamics. These collective findings underscore the importance of coordinated monitoring efforts, inclusive of both scientific and citizen-based approaches, to better understand and manage marine biodiversity shifts in the Mediterranean.